EKSTERNAL SAPI BALI BETINA - Panji B.S Hasan; Safriyanto Dako (Gorontalo Journal of Equatorial Animals, 2026)
Bali cattle are a favorite among breeders due to their good adaptability to various environmental conditions, good feed utilization, high reproductive capacity, and high carcass yield. The purpose of this study was to determine the qualitative characteristics of female Bali cattle using descriptive analysis. This study was conducted in Bolaang Uki Regency from September to October 2024. Fifty female Bali cattle were used as study subjects. The observed variables were external characteristics: coat color, leg color and pattern, calf line, horn shape, ear shape, and hoof color. The coat color, leg color and pattern, calf line, horn shape, ear shape, and hoof color of female Bali cattle varied from brick red to brown, with 4.16% being white. The leg color and pattern conformed to general standards for female Bali cattle. The calf line on the back was medium in length